Early and recurrent hospitalization after kidney transplantation: Analysis of a contemporary canadian cohort of kidney transplant recipients. Issue 8 (6th July 2020) - Bergman, Joel; Tennankore, Karthik; Vinson, Amanda
Abstract: Hospital readmission is a common occurrence following kidney transplantation, but less is known about the predictors of early and recurrent hospitalization. We analyzed a cohort of adult kidney transplant recipients in Nova Scotia, Canada, from January 2010 to December 2015. Readmission rates for 30 days, 6 months, and 1 year were calculated as a proportion of total transplants. Factors independently associated with early readmission were investigated using multivariable Cox hazards models with multivariable Anderson‐Gill Cox models being used for factors independently associated with recurrent readmission. Of the 213 patients included, 41 (19.2%), 78 (36.6%), and 88 (41.3%) were readmitted to hospital within 30 days, 6 months, and 1 year, respectively. On multivariable analyses, a history of congestive heart failure (HR 1.741, 95% CI 1.039‐2.918), peptic ulcer disease (HR 2.290, 95% CI 1.054‐4.973), and liver disease (HR 2.492, 95% CI 1.162‐5.344) was associated with higher risk of first rehospitalization. Recurrent hospital admission was associated with initial hospital duration ≥ 8 days (HR 2.140, 95% CI 1.265‐3.618), congestive heart failure (HR 1.366, 95% CI 1.044‐1.787), and liver disease (HR 1.785, 95% CI 1.257‐2.534). Increasing duration of initial hospitalization, congestive heart failure, and liver disease are important to consider when evaluating a patient's risk for recurrent readmission following kidney transplant.